Perbandingan Nilai UTS Dan UAS Pembelajaran Matematik SD -1 Mahasiswa Semester III Program Studi Pendidikan Guru Sekolah Dasar - Pao Ali, Johanis (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2026)
This study aims to find out the Difference in Mid-Semester Exam Scores (UTS) and Final Semester Exam Scores (UAS) Mathematics Learning for Elementary -1 Students in Semester III of the Elementary School Teacher Education Study Program (PGSD), Teacher Training and Education College of Terang Bangsa (STKIP) for the 2025/2026 Academic Year. The research used was an independent sample t-test to see if there was a difference or comparison between the Mid-Semester Exam (UTS) and the Final Semester Exam (UAS) of the elementary -1 mathematics learning course. A sample of 11 third semester students consisting of 3 males and 8 females data was taken from the Mid-Semester Exam Score (UTS) and Final Semester Exam Score (UAS) of the mathematics learning course for the elementary school -1 Academic Year 2025/2026. The results of the analysis show that the Mid-Semester Exam Score (UTS) is in the poor category, the Final Semester Exam (UAS) score is in the fairly good category. The results of the study showed that there was a significant difference between the Mid-Semester Exam Score (UTS) and the Final Semester Exam (UAS) Grade for Elementary School Mathematics Learning -1 Academic Year 2025/2026. The recommendation in this study is that there is a significant difference between the mid-semester exam score (UTS) and the Final Semester Exam (UAS) score, so it is highly expected that the relevant parties will improve it even more.